L’épuisabilité des ressources naturelles comme pierre d’achoppement du développement: exemplification théorique dans le domaine du tourisme de nature - Manu Tranquard (VertigO)
Nature based tourism is a form of tourism that uses the natural environment to be realized. Natural resources are at the base of the supply, and consequently, the sustainability of these resources becomes a primary and limiting factor of the economic cycle of the activity. However, while the historical construction dynamic of the concept of sustainable development has always seemed to involve questions about the exhaustion of environmental resources, the reflection on the modalities of their operational evaluation and their practical management can lead to make the Bioeconomy theory the most relevant analytical framework regarding the specificities of nature tourism. Thus, the purpose of the present contribution is to present the historical and theoretical references that establish the consubstantial link between development and natural resources to put them into perspective with the theories of sustainable tourism. It is also a question of analyzing the operational consequences of such a theoretical framework with regard to the maintenance of the attractiveness of territories through the preservation of resources, but also the knowledge of environmental impacts as a prerequisite to their mastery; and generally regarding the implementation of the criteria of tourism sustainability.